Protecting the right to occupational health in the face of the development of digital working time: the fight against the denaturalization of the limits of working and rest time - López Ahumada, José Eduardo (2024)
This research paper analyses how the digitalization of production processes affects the variables of working time and occupational health. It focuses on the flexibility of the working day and its impact on new digital work environments. Flexibility is used to create models of irregular distribution of working time. The study seeks to fairly apply working time regulations, avoiding denaturalizing the legal limits of the working day and ensuring that there are no negative effects on occupational health and safety. It also addresses practical problems arising from the confusion between working time and the private life of workers.